Quantitative evaluation of the ability of ionic liquids to offset the cold-induced unfolding of proteins - Kumar, Awanish; Rani, Anjeeta; Venkatesu, Pannuru; Kumar, Anil (Physical Chemistry Chemical Physics, 2014)
Significant non-reversible two-state denaturation was observed for proteins such as myoglobin (Mb) and alpha-chymotrypsin (CT) with decreasing temperature in the presence of 1-butyl-3-methylimidazolium-based ([C(4)mim]X-+(-)) ionic liquids (ILs) with various anions (X-). Interestingly, for the first time, ILs having acetate and bromide anions were proven to counteract the cold-induced unfolding of proteins.